2018
DOI: 10.1039/c7nj04208f
|View full text |Cite
|
Sign up to set email alerts
|

Designing model imino bifunctional chelators for radiopharmaceuticals –in vitroantitumor activity, photoluminescence and structural analysis

Abstract: Designed bifunctional chelators for the radionuclides of 188/186Re or 99mTc. Structure, DFT calculations, antitumor and imaging properties are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Previously ((1), in the form of powder) has been investigated and demonstrated to have a quantum yield of 1.3% and 0.9% at 390 nm and 280 nm. 31 Reproducibility of the quantum yield of (1) in both forms (powder vs. crystalline) has been conrmed. The morphology of a luminescent material may have a strong effect on its emission intensity, e.g.…”
Section: Photoluminescencementioning
confidence: 99%
See 2 more Smart Citations
“…Previously ((1), in the form of powder) has been investigated and demonstrated to have a quantum yield of 1.3% and 0.9% at 390 nm and 280 nm. 31 Reproducibility of the quantum yield of (1) in both forms (powder vs. crystalline) has been conrmed. The morphology of a luminescent material may have a strong effect on its emission intensity, e.g.…”
Section: Photoluminescencementioning
confidence: 99%
“…UV-Vis (nm, L mol À1 cm À1 ): l max ¼ 397, 3 ¼ 7.686 Â 10 2 . 31 6). ReAA (0.0500 g, 6.489 Â 10 À2 mmol) was dissolved in methanol (5 ml).…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, several related compounds have been reported that include (E)-N-benzylidene-1H-1,2,4-triazol-5-amine as the main skeleton, viz. 5-methyl-2-[(1H-1,2,4-triazol-3-ylimino)methyl]phenol (PEVXAS; Brink et al, 2018) Symmetry codes: (i) x À 2; y; z; (ii) x À 1; y; z.…”
Section: Database Surveymentioning
confidence: 99%
“…Pyridyl based type of ligands have contributed a great deal across many fields [9][10][11][12]. Subsequently, a great deal of interest towards multi-dentate pyridyl based ligands has grown over the decades across many disciplines including photoluminescence [13], medicinal chemistry [14], catalysis [15,16] and radiopharmaceutical [17] chemistry, also as pursued in our research group [18][19][20]. It is for this evidence that the tailoring of the multi-dentate ligands are still of paramount importance.…”
Section: Commentmentioning
confidence: 99%